Morphological Agronomy Character Of Gene Mutation Of Various Varieties Of Soybean (Glycine Max L) On Drought Stress - Aminah Aminah; Marliana S Paad (UNIVED Press, Dehasen University Bengkulu, 2022)
The research objective is to identify the responsiveness of mutated soybean varieties to the growth and production, which are tolerant to drought stress. The research was held in the experimental garden of the Agricultural Technology Development Center, Maros Regency, using a randomized block design method consist of three treatments: M1 Anjasmoro, M1 Argomulyo and M1 Dena-1. The selection method carried out by leaving the treatment of plants resulting from gamma ray irradiation mutant-1, also the plants were not given water until entered the first generative phase (R1) and showed symptoms of severe wilting. having shown the symptoms, then the plants were given water again to see their recovery. The results showed the best morphological character against drought stress was M1 Dena-1. However, for the growth and production parameters, M1 Anjasmoro was the best. M1 Anjasmoro plant height 86.00 cm, the number of leaves 21,22 strands, plant dry weight 177.54 grams, the fastest flowering age 35.50 days. M1 Anjasmoro gave the best results for the parameters of 100 seeds weight (21.50 grams), seed weight per plant (18.52 grams), seed weight per plot (1.39 kg) production per hectare (2.38 tons), and the fastest harvesting age was obtained in M1 Anjasmoro (83,33 days).